DEVELOPMENT OF MULTIPLE INTELLIGENCE-BASED LEARNING BY RESEARCH MODEL IN ISLAMIC EDUCATION CURRICULUM - Efendy, Rustan; Karim, Abdul Rahim; D, Muh Akib; Herman, Arfian Alinda; Nur, Fakhriyah; Arhad, Muhammad (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Low student engagement in research and limited accommodation of diverse intelligences are key challenges in Islamic higher education, hindering inclusive and productive learning. Purpose: This study aims to develop a Learning by Research model integrated with Multiple Intelligence theory to enhance students’ research and scientific publication skills while optimizing their diverse intellectual potentials. Method: Using a Research and Development (R&D) approach, the model was developed and tested through iterative stages, including expert validation, limited trials, and broader implementation in experimental classes. Results: The model significantly improved students’ research skills, scientific article writing, and engagement of multiple intelligences, with average performance rising from 60% to 85%. It emphasizes six key aspects: integration of theory and practice, student-centered learning, stakeholder collaboration, technology utilization, adaptive learning, and scientific publication orientation. Conclusion: This model offers a transformative, inclusive approach to curriculum design in Islamic higher education, fostering research culture and addressing contemporary educational challenges.